EL INCUMPLIMIENTO DE LOS PLAZOS PROCESALES EN EL DEBIDO PROCESO Y EN LA TUTELA JURISDICCIONAL EFECTIVA DE LA TERCERA SALA PENAL REOS LIBRES DE LA CORTE SUPERIOR DE JUSTICIA DE LIMA, PERIODO 2016-2017 - BENAVIDES AMPUERO, CHRISTIAN PAUL (2020)
At this point of the present investigation, we will delve into the scope of the constitutional guarantee of the process, for this it is necessary to define what a "constitutional guarantee" is. In principle, when we talk about constitutional guarantee we immediately think of habeas corpus, amparo, habeas data, etc .; that is, in procedural instruments that fulfill the function of directly protecting fundamental rights. Having said this, it is necessary to point out that regarding procedural guarantees, they are established as entities that are particularly distinct from the constitutional guarantee process. However, seen from the civil process, we refer to the term effective jurisdictional protection and due process, these two are fundamental rights in the political Constitution of Peru, so they are understood as constitutional guarantee. Political Constitution of Peru, 1993 Thus, Due Process and Effective Jurisdictional Guardianship also include other guarantees that would provide and ensure the legal security that will protect “fundamental rights within the judicial process; the guarantees of an independent judge without neglecting the impartiality, likewise, of the motivation of judicial decisions, of plurality of instance, of presumption or state of innocence, of the right of defense, of respect for dignity, respect for dignified life, free exercise of the defense with dignity ”, etc., in this way will ensure the validity of the human rights that they themselves comprise. For the reasons stated above, I consider this point particularly interesting and relevant to investigate, since the results obtained contribute significantly to the actions of justice operators, in the way a process is developed, in addition to influencing the interpretation of the norm and the right to apply when issuing judgments.